IMPROVING THE INTERACTION OF PUBLIC AUTHORITIES AND LOCAL SELF-GOVERNMENT ORGANIZATIONS ON SOCIAL ISSUES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article examines the interaction of public authorities and local self-government on social issues, taking into account the main conceptual positions on the development and organization of local self-government. These interactions should meet two main social needs: the realization of the right of citizens to participate in the management of local affairs; the creation of an effective system of local representative government capable of meeting the vital local needs of the population and the development of the state.
Keywords: Local government, basic conceptual positions, public authorities, improvement of the budget and tax system, Tax Code of the Kyrgyz Republic, tax service, objects of taxation and taxpayers.